(3Odjd GdeOjQ GdYQHj dEOGQI GdhbJ (B/s - (3MehOI, YHO GdfGUQ eMeOs ((3GdbGgQI(B: s (3GdefXeI GdYQHjI ddJfejI GdEOGQjI(B, s, 2003)
(3EOGQI GdhbJ GdESJQGJjLjI GdYGeI(B- (3EOGQI GdhbJ(B- (3GdJUOj ddeVjYGJs
Keywords: (3EOGQI GdhbJs; (3GdhbJ(B- (3GdEOGQI hGdeOjQjf(B- (3GdOhd GdYQHjIs